Jenis Tumbuhan Pakan dan Tempat Beristirahat Macaca fascicularis di Kawasan Kebun Campuran - Santi Nurul Kamilah; Jarulis Jarulis; Yili Sarti (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to inventory the types of plants used as food and resting place by Macaca fascicularis in the mixed garden area of ​​Chief Curup Village, Rejang Lebong Regency, Bengkulu. The method used is the Continuous-time recording method and focal animal sampling which is focused on four target individuals in the observed group. The results showed that the plants used by M. fascicularis as a food source were Arenga pinnata, Schizostachyum brachycladum, Capsicum frutescens, Durio zibethinus, Archidendron pauciflorum, Terminalia catappa, Garcinia mangostana, Musa paradisiaca, Parkia speciosa, ferns from the order Cyatheales and Hibiscus tiliaceus. While the plants used as resting places were Durio zibethinus, Terminalia catappa and Schizostachyum brachycladum. In conclusion, there are 11 types of plants that are used as food sources by M. fascicularis (fruit, flowers, leaves, petioles), and 6 of them are community cultivated plants. In addition, there are two types of plants that are used as a place to rest during the day and one type of plant as a place to sleep at night. Keywords: Macaca fascicularis, Long Tailed Monkey, Forage Plants